(untitled) (Journal of the Sociology and Theory of Religion, 2019)
The purpose of this paper is to study the relationship between the foundations of voluntarist philosophy and the development of ideological utopias, especially when determining the development of a secular cult whose faith rests on politics as an instrument of collective salvation. The thesis of the article is that the nominalist disconnection of reality will allow the sublimation of a new anthropological and legal paradigm that must necessarily break with the past metaphysical order, inaugurating a materialist eschatology that prolongs modern subjectivity while dissolving into the indetermination of the public, destroying the essence of the political by administering and bureaucratising all human events.